Political financing reform: Politics, policies, and patronage in Malaysia - DETTMAN, Sebastian Carl (Institutional Knowledge at Singapore Management University, 2020)
This article analyses the evolution of political finance reform debates in Malaysia, one of the world’s most durable electoral authoritarian regimes. While the reliance of the dominant party, UMNO, on unfettered resources remained unchanged, crises in Malaysia’s political environment allowed civil society actors to concretise abstract debates over reform into specific proposals. Drawing from interviews, public statements and observation, two distinct periods in this reform debate are analysed: after Najib Razak assumed power in 2009, following the unprecedented electoral success of the opposition during the 2008 general election; and after the 1MDB scandal broke in 2015. In both periods, civil society actors took advantage of new political dynamics to present specific proposals for political finance reform. These proposals laid the groundwork for government-led reform recommendations, though key provisions were excised that would curb UMNO’s power. Reform efforts stalled when the government resisted deeper reform while opposition parties offered little support for the proposed changes. This article reviews an under-researched area of policy interactions in electoral authoritarian regimes involving not just the ruling party and the opposition, but also civil society. A postscript considers the trajectory of this debate following the 2018 national elections which toppled UMNO from power.